2021
DOI: 10.1038/s41598-021-96678-w
|View full text |Cite
|
Sign up to set email alerts
|

Non-respiratory particles emitted by guinea pigs in airborne disease transmission experiments

Abstract: Animal models are often used to assess the airborne transmissibility of various pathogens, which are typically assumed to be carried by expiratory droplets emitted directly from the respiratory tract of the infected animal. We recently established that influenza virus is also transmissible via “aerosolized fomites,” micron-scale dust particulates released from virus-contaminated surfaces (Asadi et al. in Nat Commun 11(1):4062, 2020). Here we expand on this observation, by counting and characterizing the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Our current findings (i.e. skin-shedding and clothing being a dominant source of particles from humans), combined with the findings from previous studies on the presence and resuspension of pathogens from clothing and skin surfaces, ,, suggest that non-respiratory sources could also play a role in the airborne transmission of pathogens, in addition to respiratory aerosol emissions. However, given the lack of measurements of any pathogens in our study, this is only a hypothesis which warrants that more systematic studies are needed to characterize the non-respiratory fraction of aerosols emitted from humans to investigate if and to what extent they can contribute to the spread of infectious diseases.…”
Section: Implications and Limitationssupporting
confidence: 79%
See 2 more Smart Citations
“…Our current findings (i.e. skin-shedding and clothing being a dominant source of particles from humans), combined with the findings from previous studies on the presence and resuspension of pathogens from clothing and skin surfaces, ,, suggest that non-respiratory sources could also play a role in the airborne transmission of pathogens, in addition to respiratory aerosol emissions. However, given the lack of measurements of any pathogens in our study, this is only a hypothesis which warrants that more systematic studies are needed to characterize the non-respiratory fraction of aerosols emitted from humans to investigate if and to what extent they can contribute to the spread of infectious diseases.…”
Section: Implications and Limitationssupporting
confidence: 79%
“…Our chamber experiments further show that most of the particles directly emitted by humans are nonrespiratory in origin. Numerous studies have reported the presence, as well as the resuspension of pathogens (bacterial and viral) from clothing. Asadi et al , demonstrated that aerosolized fomites produced from contaminated body surfaces contribute to airborne transmission of influenza in guinea pigs. Our current findings (i.e.…”
Section: Implications and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We report a rise in <0.53 μm particles and a drop in particles in the 1-10 μm range after infection. One of the caveats of these measurements in small animals is that detected particles may come from aerosolized fomites, and residual dust generated by movement [33]. In our system, we did not detect any particles originating from dead animals or the environment, but we also saw a noticeable reduction of particles across sizes when movement was minimal, or animals were deeply asleep.…”
Section: Discussionmentioning
confidence: 69%
“…For instance, clothing accumulated inhalable and respirable particles (≤10 μm) from indoor air in experiments, which were then resuspended during typical human activities. Such resuspension may have caused airborne SARS-CoV-2 genetic material (RNA) in protective-apparel removal rooms in a hospital environment . Resuspension (or “aerosolized fomite”) is also a suspected cause of the transmission of SARS-CoV-2 and influenza virus in controlled animal studies. However, the potential for clothing to transmit SARS-CoV-2 between humans remains an open question …”
Section: Introductionmentioning
confidence: 99%